Paradoxical embolic stroke during catheter-directed thrombolytics in a patient with massive pulmonary embolism: A case report - Atefeh Ghorbanzadeh; Emily C Bendel; Damon E. Houghton (Brain Circulation)
Paradoxical embolism represents a critical and potentially fatal complication that can be associated with pulmonary embolism (PE). This case details a unique case of massive PE, further complicated by embolic stroke occurring during catheter-directed thrombolytic therapy. There was no evidence of thrombosis during the initial evaluation with lower extremity Doppler ultrasound, abdominal computed tomography scan, and transthoracic echocardiography. Differentials for the source of the emboli include unrecognized left atrial appendage thrombus, pulmonary arteriovenous malformations, and a patent left foramen ovale. Our findings highlight the complexities and treatment challenges of massive PE.